Human hours : poems - Barnett, Catherine, 1960- (Graywolf Press, 2018)
"Catherine Barnett's tragicomic third collection, Human Hours, shuttles between a Whitmanian embrace of others and a kind of rapacious solitude. Barnett speaks from the middle of hope and confusion, carrying philosophy into the everyday. Watching a son become a young man, a father become a restless beloved shell, and a country betray its democratic ideals, the speakers try to make sense of such departures. Four lyric essays investigate the essential urge and appeal of questions that are “accursed,” that are limited- and unanswered- by answers. What are we to do with the endangered human hours that remain to us? Across the leaps and swerves of this collection, the fevered mind tries to slow- or at least measure- time with quiet bravura: by counting a lover's breaths; by remembering a father's space-age watch; by envisioning the apocalyptic future while bedding down on a hard, cold floor, head resting on a dictionary. Human Hours pulses with the absurd, with humor that accompanies the precariousness of the human condition."--Amazon.com.